Being the finger pointing to the moon: how martial arts can provide a holistic perspective on teachers' role in tackling sustainability challenges - Shpak, Guy; Vasques, Ana (Frontiers in Education, 2023)
From social injustice to climate crisis, our modern society currently face an unprecedented magnitude of global challenges. To properly support future generations, long-term solutions must take into account the role of education systems in developing necessary competencies needed for future world citizens. Pedagogical methodologies should reflect this need and adapt accordingly, focusing on developing intrapersonal and implementation capabilities that are acknowledged as sustainabilityrelated competencies. While some educational approaches are better tuned to develop these skills, the deployment and effectiveness of these might be limited by the perception of the teacher's position in the classroom. Given the urgency of the situation, we propose to use educational principles that have already proved effective in developing similar skills for decades and centuries, and inspired by the world of martial arts. Rather than incorporating martial arts elements per se, we argue that by adopting key principles taken from traditional martial arts pedagogies, we can redefine the teacher's educational function, and by that redefine the nature of the student's learning process in a way aligned with acquiring sustainability-related competencies. We propose a conceptual framework that distills relevant elements from martial arts methodologies and defines ways to implement these in academic education systems.